STORYTELLING AS A PEDAGOGICAL TECHNIQUE IN IMPROVING STUDENTS’ SPEAKING SKILLS IN SUBURBAN SECONDARY SCHOOLS - Yakhiyarov, Alimzhan; Doganay, Yakup (Pedagogy and Psychology, 2023)
The aim of the study was to find out the influence of storytelling on improving students’ speaking skills in Kazakhstani suburban secondary schools. Speaking is considered as one of the most challenging skills of four language skills. Scholars identified several reasons for difficulties in developing speaking competence. First is fear of making mistakes, second reason is passive participation of learners in English classrooms, and third is L1 interference. Scholars found various solutions to solve the issues that they had detected and one of them is using the technique of storytelling at EFL lessons to improve students’ speaking skill. The quasi-experimental research was used to examine whether the storytelling technique has positive impact on students’ speaking skills. There were two groups: experimental groups, where students were taught with the help of the storytelling technique, whereas the control group students were taught in traditional way. The findings of the study revealed that the storytelling technique has a positive impact on students’ speaking skills, they have improved their communicative competence, enlarged vocabulary, enhanced pronunciation and fluency. Their perception of learning with storytelling technique was efficient, their motivation to learning English increased, which is essential in overcoming the challenges that they come across with in EFL classroom. Implementing storytelling technique makes learners more active and enthusiastic in carrying out tasks in classroom. Moreover, students often share what they have learnt during the class with family and friends outside the lessons as well.